Excess glucose inhibits the cotyledon greening of etiolated seedlings - Zi-Meng Yao; Hu-Hui Chen (Plant Signaling & Behavior)
The capability of the transition from skotomorphogenesis-to-photomorphogenesis (de-etiolation) is requisite for seedling survival and development. However, how carbohydrate in germinating seeds controls seedling de-etiolation remains unclear. Mu et al. (2022) investigated the regulatory roles of soluble sugars (such as, glucose or sucrose) on de-etiolation during the transition from skotomorphogenesis-to-photomorphogenesis. The authors revealed that in the dark, sucrose/glucose in germinating seeds induces ethylene production/signaling. Ethylene signaling promotes the stability of EIN3 (ETHYLENE-INSENSITIVE3), a key component in the ethylene signaling pathway. In turn, EIN3 directly binds to the promoter of SUC2 (Sucrose Transporter 2), encoding a major sucrose transporter, to repress SUC2 transcription. The resulting phloem loading of sucrose is blocked, and thereby the accumulation of sucrose is elevated in etiolated seedling cotyledons. When exposed to light irradiation, accumulated sucrose/glucose inducing ethylene elevates the stability of EIN3, repressing phyA (encoding the photoreceptor of a far-red light/the inhibitor of a cotyledon greening) expression to promote de-etiolation. In this study, we mainly discuss the findings (low sugars promote de-etiolation) of Mu et al. (2021) and further find that excess sugars inhibit de-etiolation.